Analysis Effectiveness Policy Subsidy Agriculture to Income Farmers in Indonesia - Prahitaningtyas, Sherina; Olasoji, Timilehin (Politeknik Siber Cerdika Internasional, 2024)
Policy subsidy agriculture in Indonesia has long been implemented as effort For support productivity and well-being farmers . Although Thus , the effectiveness subsidy This in increase income farmer Not yet fully optimized. Research This aiming For analyze how much effective policy subsidy agriculture in increase income farmers and identify factors that influence success or obstacle in implementation . Research use method quantitative descriptive with data collection through survey to farmer recipient subsidies in various regions of Indonesia as well as secondary data analysis from the Ministry of Agriculture and the Central Bureau of Statistics . The results of the study show that although subsidy lower part small from cost production , increase income farmer Not yet significant . Distribution subsidies that are not evenly be one of reason main ineffectiveness policy this , especially in areas with access limited . Findings This indicates the need repair in mechanism distribution subsidies and development approach based on need area specific for ensure more impact​ evenly to income and welfare farmers . Research This give recommendation For optimization policy more subsidies​ efficient in support resilience food national and improvement welfare farmer